Expression, purification, crystallization and preliminary X-ray analysis of full-length human RIG-I - Kwok, Jane (2015)
The human innate immune system can detect invasion by microbial pathogens through pattern-recognition receptors that recognize structurally conserved pathogen-associated molecular patterns. Retinoic acid-inducible gene I (RIG-I)-like helicases (RLHs) are one of the two major families of pattern-recognition receptors that can detect viral RNA. RIG-I, belonging to the RLH family, is capable of recognizing intracellular viral RNA from RNA viruses, including influenza virus and Ebola virus. Here, full-length human RIG-I (hRIG-I) was cloned in Escherichia coli and expressed in a recombinant form with a His-SUMO tag. The protein was purified and crystallized at 291 K using the hanging-drop vapour-diffusion method. X-ray diffraction data were collected to 2.85 Å resolution; the crystal belonged to space group F23, with unit-cell parameters a = b = c = 216.43 Å, [alpha] = [beta] = [gamma] = 90°.